Do "mudsplashes" induce tactile change blindness? - Gallace, A; Tan, H; Spence, C (2007)
The phenomenon of change blindness (the surprising inability of people to correctly perceive changes between consecutively presented displays), primarily reported in vision, has recently been shown to occur for positional changes presented in tactile displays as well. Here, we studied people's ability to detect changes in the number of tactile stimuli in successively presented displays composed of one to three stimuli distributed over the body surface. In Experiment 1, a tactile mask consisting of the simultaneous activation of all seven possible tactile stimulators was sometimes presented between the two to-be-discriminated tactile displays. In Experiment 2, a "mudsplash" paradigm was used, with a brief irrelevant tactile distractor presented at the moment of change of the tactile display. Change blindness was demonstrated in both experiments, thus showing that the failure to detect tactile change is not necessarily related to (1) the physical disruption between consecutive events, (2) the effect of masking covering the location of the change, or (3) the erasure or resetting of the information contained within an internal representation of the tactile display. These results are interpreted in terms of a limitation in the number of spatial locations/events that can be consciously accessed at any one time. This limitation appears to constrain change-detection performance, no matter the sensory modality in which the stimuli are presented.